Penerapan Strategi Visual Phonics untuk Pengenalan Huruf Bilabial bagi Anak Tunarungu di SLB Negeri Cicendo - Nurfadilah, Agni; Diana Aprilia, Imas; Gunawan, Dudi (Inspirasi : Jurnal Pendidikan dan Kebudayaan, 2025)
Hearing impairment often leads to language delays, particularly in letter recognition skills. Empirical findings revealed that the subject of this study was only able to identify vowel letters and the bilabial consonant /m/. Previous learning strategies applied an expository approach through lectures, which proved ineffective in achieving the intended learning outcomes. This study aims to examine the effectiveness of the visual phonics strategy in improving the ability to recognize bilabial letters /p/ and /b/ among second-grade deaf students at SLB Negeri X, Bandung. The research employed a Single Subject Research (SSR) method with an A-B-A design. The subject was a deaf child with a profound hearing loss (>90 dB). The results showed that the application of the visual phonics strategy significantly enhanced the subject's ability to articulate, signal, and visually identify bilabial letters when prompted by the researcher, as well as recognize these letters within functional words. Improvement was evident through increased mean levels across phases, supported by intra- and inter-condition analyses. Visual phonics, as a multisensory and interactive learning approach, proves to be an effective alternative for phoneme instruction among deaf children.